Tuple calculus for multiset table algebra - Lysenko, І.M. (PROBLEMS IN PROGRAMMING, 2024)
This paper is a logical continuation of research devoted to the actual problem of developing the theoretical foundations of table (relational) databases. The issue of using multisets in table databases is important and relevant. Many database-oriented languages require a relational model with multiset semantics. There are many applied problems, the feature of which is multiplicity and repeatability of data. For example, these are sociological polls of different population groups, calculations on DNA, and others. In this context, the question of constructing a tuple calculus for a multiset table algebra is considered, in which the concept of a table is refined using the concept of a multiset. In the article, the formalization of tuple calculus for multiset table algebra is carried out. The alphabet, and the syntax of terms, atoms, and formulas are defined. A set of legal formulas is introduced through the concept of the free and bound variable. The concept of a scheme and set of attributes with which a tuple variable occurs in a formula are also introduced. The definition of tuple calculus expression for multiset table algebra is given, according to which it is a multiset of tuples that satisfy the condition defined by the legal formula. The article provides rules for determining the number of tuple duplicates in the resulting multiset. Another important result consists in proving that constructed tuple calculus is as expressive as multiset table algebra. This research opens up new possibilities for database theory development and may be useful for information technology and database professionals. It contributes to a deeper understanding of construction query principles, an important aspect of modern computer science and industry.Prombles in programming 2024; 2-3: 28-36